A Gain-of-Function Mutation of Arabidopsis CRYPTOCHROME1 Promotes Flowering(1)([W])([OA]) - Exner, Vivien (American Society of Plant Biologists, 2010)
Plants use different classes of photoreceptors to collect information about their light environment. Cryptochromes are blue light photoreceptors that control deetiolation, entrain the circadian clock, and are involved in flowering time control. Here, we describe the cry1-L407F allele of Arabidopsis (Arabidopsis thaliana), which encodes a hypersensitive cryptochrome1 (cry1) protein. Plants carrying the cry1-L407F point mutation have elevated expression of CONSTANS and FLOWERING LOCUS T under short-day conditions, leading to very early flowering. These results demonstrate that not only the well-studied cry2, with an unequivocal role in flowering promotion, but also cry1 can function as an activator of the floral transition. The cry1-L407F mutants are also hypersensitive toward blue, red, and far-red light in hypocotyl growth inhibition. In addition, cry1-L407F seeds are hypersensitive to germination-inducing red light pulses, but the far-red reversibility of this response is not compromised. This demonstrates that the cry1-L407F photoreceptor can increase the sensitivity of phytochrome signaling cascades. Molecular dynamics simulation of wild-type and mutant cry1 proteins indicated that the L407F mutation considerably reduces the structural flexibility of two solvent-exposed regions of the protein, suggesting that the hypersensitivity might result from a reduced entropic penalty of binding events during downstream signal transduction. Other nonmutually exclusive potential reasons for the cry1-L407F gain of function are the location of phenylalanine-407 close to three conserved tryptophans, which could change cry1’s photochemical properties, and stabilization of ATP binding, which could extend the lifetime of the signaling state of cry1.